The potential distributions of African Azolla species and their implications for African wetland ecosystems for the future. Issue 8 (22nd August 2022) - Karichu, Mwihaki J.; Ngarega, Boniface K.; Onjalalaina, Guy E.; Kamau, Peris; Sessa, Emily B.
Abstract: Climate change is predicted to affect species in aquatic ecosystems. In Africa, factors that may influence the responses of aquatic species are poorly studied and challenging to predict. In this study, we examined the potential distribution of three aquatic fern species in the genus Azolla in Africa under projected climate change scenarios. MaxEnt was used to create ecological niche models of the three species using occurrence data and environmental variables. All models had satisfactory AUC and TSS values, indicating high prediction precision (AUC and TSS > 0.801). Results showed that elevation and precipitation were the most important variables limiting the species' expansion in the future. In addition, we observed significant variations in the climatic niches of the three species and their distinct climatically appropriate regions. The current potential distribution ranges for the species varied between 2, 328, 726 km 2 and 4, 026, 363 km 2 . According to the model predictions for the current period, the potential range of Azolla species extended outside the known and recorded locations; however, under future climate conditions, the species were projected to lose between 8.1% and 48% of their suitable habitats due to climate change. Our findings can be used to develop sustainable conservation measures for aquatic species and raise awareness about the effects of climate change. Abstract : In this paper we modeled the distribution of Azolla in Africa under climate change scenarios. The prediction results showed that Azolla species will be affected by climate change. Urgent conservation measures are required.